Translating and testing the Alberta context tool for use among nurses in Swedish elder care - Eldh, Ann C; Ehrenberg, Anna; Squires, Janet E; Estabrooks, Carole A; Wallin, Lars (Université d'Ottawa | University of Ottawa, 2013)
Abstract Background There is emerging evidence that context is important for successful transfer of research knowledge into health care practice. The Alberta Context Tool (ACT) is a Canadian developed research-based instrument that assesses 10 modifiable concepts of organizational context considered important for health care professionals’ use of evidence. Swedish and Canadian health care have similarities in terms of organisational and professional aspects, suggesting that the ACT could be used for measuring context in Sweden. This paper reports on the translation of the ACT to Swedish and a testing of preliminary aspects of its validity, acceptability and reliability in Swedish elder care. Methods The ACT was translated into Swedish and back-translated into English before being pilot tested in ten elder care facilities for response processes validity, acceptability and reliability (Cronbach’s alpha). Subsequently, further modification was performed. Results In the pilot test, the nurses found the questions easy to respond to (52%) and relevant (65%), yet the questions’ clarity were mainly considered ‘neither clear nor unclear’ (52%). Missing data varied between 0 (0%) and 19 (12%) per item, the most common being 1 missing case per item (15 items). Internal consistency (Cronbach’s Alpha > .70) was reached for 5 out of 8 contextual concepts. Translation and back translation identified 21 linguistic- and semantic related issues and 3 context related deviations, resolved by developers and translators. Conclusion Modifying an instrument is a detailed process, requiring time and consideration of the linguistic and semantic aspects of the instrument, and understanding of the context where the instrument was developed and where it is to be applied. A team, including the instrument’s developers, translators, and researchers is necessary to ensure a valid translation. This study suggests preliminary validity, reliability and acceptability evidence for the ACT when used with nurses in Swedish elder care.